El cuerpo en perspectiva de una subjetivación política. Un ámbito de estudio de la Educación Corporal (2011)
ABSTRACT: This is a plot fed by three concepts that allows the elaboration of the network of what is coming problematizing as Education of the Body. In it, is done a philosophical approach which takes up, briefly, authors such as José Ortega y Gasset, Jacques Rancière and Michel Foucault, and other pedagogy based on the contributions of Jorge Larrosa, Fernando Bárcena and Carlos Skliar, who from various edges, point to the configuration of new narratives that allow us to reach a crytical thinking on the relationship between body and education.